Documental sobre la “violencia intrafamiliar” - Villón Pilco, Xiomara Virginia (2010)
Family means that group of people with links that may be blood relatives, interactions or effectives. "Domestic violence can be defined as a situation of abuse of power or physical or psychological abuse of a family member around. Can be manifested through coups and serious incidents, as well as insults, economic management, threats, blackmail, control activities, sexual abuse, insolation from family and friends, prohibition to work outside the home, emotional abandonment, humiliation or failure opinions." currently there are an endless number of intrafamily assaults, only in guayaquil, the studies show that during january to september 4.055 there were reports of battered woman which are 95% of the total. This project presents real stories of people involved, specialists and other power capable of solving problems of this magnitude, in addition to displaying the information provided by institutions that offer this kind of social aid. The documentary would capture the impact generated by this type of domestic assault to raise awareness both in specialized institutions as the people involved, in order to improve family communication.